Migration Effects Cause Linear Waveform in Cyclic Voltammetry of Metal Anode Electrodeposition/Dissolution without Supporting Electrolyte: Calculations and Experiments on a Model Case - Yuko YOKOYAMA; Masahiro YAMAMOTO; Kenji KANO (Electrochemistry)
Cyclic voltammetry of metal anode electrodeposition/dissolution often gives a linear waveform in the absence of supporting electrolyte. For a one-electron redox model system without supporting electrolyte, in which both redox species are soluble and the oxidized form is zero-valent, finite different numerical calculations on the Nernst–Plank–Poisson equation have revealed that migration effects almost entirely counteract the driving force potential to exhibit such linear waveforms in voltammetry. In the calculation the dumping Newton–Raphson method was used to avoid numerical divergence. The voltammetric response calculated on the model system was verified experimentally in a ferrocene-derivative redox system that yields a soluble zero-valent reductive product. An approximate interpretation of the linearity was also proposed.